Students’ Perception of E-learning During Covid-19 Pandemic - Angga Hidayat (Universitas Teknokrat Indonesia, 2020)
The objectives of the study are (1) to investigate students’ perceptions of the use of e-learning during covid-19 quarantine in accounting department at Pamulang University, (2) to investigate e-learning motivation during covid-19 quarantine in accounting department at Pamulang University. The research is an ex-post facto study conducted in accounting deparment at Pamulang University. Variables in the study consist of independent variable and dependent variable respectively namely students’ perceptions of the use of e-learning during covid-19 quarantine and e-learning motivation during covid-19 quarantine. Data obtained from questionnaire about students’ perceptions and e-learning motivation during covid-19 quarantine are analyzed quantitatively. Students’ perceptions of the use of e-learning during covid-19 quarantine in accounting department at Pamulang University is in medium category. E-learning interest during covid-19 quarantine in accounting department at Pamulang University is in medium category.Keywords: Distance Learning Motivation, E-learning, Perception.